Enzymatic synthesis of dextran-containing hydrogels - Ferreira, Lino (2002)
Dextran, a natural glucose-containing polysaccharide, has been acylated by Proleather FG-F and lipase AY, a protease and lipase from Bacillus sp. and Candida rugosa, respectively, in anhydrous dimethylsulfoxide in the presence of vinyl acrylate (VA). The efficiency of the reaction in the presence of Proleather FG-F and the isolated yields were ca. 71% and 45%, respectively. Dextran derivatized with VA (dexT70-VA) was characterized by gel permeation chromatography and its structure was established by NMR indicating two positional isomers at the 2 and 3 positions on the glucose moieties in equal amounts. Furthermore, the dextran glucopyranose residues were mono-substituted. The benefits of the biocatalytic synthesis of dextran acrylates was demonstrated using 4-dimethylaminopyridine as a chemical catalyst. Gels were prepared by free radical polymerization of aqueous solutions of dexT70-VA with different degrees of substitution and monomer concentrations. Intermolecular linkages and physical entanglements are predominantly formed by concentrated solutions, however, a part of the acrylate groups did not react. Gel pore sizes were calculated from swelling experiments and ranged from ca. 18 to 182 Å.